Evidence of Climate Change Impact on Quantity of Rice-Planted Areas in Panama - SUAREZ, Ronny (Journal of Environmental Management and Tourism, 2024)
This paper provides statistical evidence of a positive correlation between anomaly precipitation and the variation of planted hectares of rice. Panamanian farmers reduce planted areas of rice when they experience lower levels of rain.